1977
DOI: 10.1085/jgp.70.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain-insensitive salt and water movements in duck red cells. III. The role of chloride in the volume response.

Abstract: A B S T a A C T This paper describes the effect of external chloride on the typical swelling response induced in duck red cells by hypertonicity or norepinephrine. Lowering chloride inhibits swelling and produces concomitant changes in net movements of sodium and potassium in ouabain-treated cells, which resemble the effect of lowering external sodium or potassium. Inhibition is the same whether chloride is replaced with gluconate or with an osmotic equivalent of sucrose. Since changes in external chloride als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 14 publications
3
29
0
Order By: Relevance
“…The loss of cell solute during volume equilibration in hypotonic medium is comparable to the gain in cell solute during volume equilibration in hypertonic medium. The latter process has been studied by Schmidt and McManus [21] in avian red blood cells and their findings are consistent with those reported in this paper. They note that the water uptake following hypertonic shrinking, which reflects changes in cellular electrolyte content, is three times more sensitive to the chloride concentration in the medium than it is to the concentration of sodium.…”
Section: Discussionsupporting
confidence: 91%
“…The loss of cell solute during volume equilibration in hypotonic medium is comparable to the gain in cell solute during volume equilibration in hypertonic medium. The latter process has been studied by Schmidt and McManus [21] in avian red blood cells and their findings are consistent with those reported in this paper. They note that the water uptake following hypertonic shrinking, which reflects changes in cellular electrolyte content, is three times more sensitive to the chloride concentration in the medium than it is to the concentration of sodium.…”
Section: Discussionsupporting
confidence: 91%
“…1 A; Tosteson and Hoffman, 1960;Funder and Wieth, 1966b;Lee et al, 1984). Therefore, for cells in the steady state, where the sum Nai + Ki is constant with time, it is possible to calculate the net driving force, A~net , for cotransport from the chemical potential gradients of Na,K, and C1 that exist across the cell membrane, using the formula: as previously proposed (Schmidt and McManus, 1977; see also Haas et al, 1982, andG6bel, 1984). The calculation assumes a cotransport stoichiometry of 1 Na/1K/2CI as found for human red cells by Garay et a].…”
Section: Discussionmentioning
confidence: 99%
“…This is in light of the fact that the cotransport system is known to promote coupled, bidirectional net movements of Na, K, and CI in response to perturbations in cell volume (Kregenow, 1981;Siebens, 1985;Hoffmann and Simonsen, 1989) and/or changes in the net chemical potential driving forces (Schmidt and McManus, 1977;Duhm and Grbel, 1984). It has been reported by others (Adragna et al, 1982;Duhm and Grbel, 1982;Stewart, 1988) that there was a significant interindividual variability in the size of the cotransport flux, and that this flux also varied inversely with both the mean red cell volume (MCV) and K content (Duhm and Grbel, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Careful kinetic studies confirmed the coupled influx of Na + and K + after cell shrinkage [284], and net flux measurements under a variety of conditions indicated a Na + : K + stoichiometry of 1: 1 [285]. Norepinephrine and other catecholamines mimick the RVI response and produce a cell swelling in isotonic medium when the external K + concentration is elevated [122,123,166,268,285,286]. The activation by norepinephrine seems to be mediated by changes in intracellular cAMP, and any agent that raises cAMP activates the cotransport system [14,168,247,248,268,277].…”
Section: Avian Red Blood Cellsmentioning
confidence: 75%